Implikasi Regulasi Perizinan Terhadap Pembatasan Starlink Dan Dampaknya Bagi Persaingan Usaha di Indonesia - Owen Edgar Kuncoro; Bambang Priyatna Kusuma (Fakultas Hukum, Universitas Warmadewa, 2025)
Starlink is a large constellation of advanced artificial satellites that work together as a single system using low Earth orbit to provide high speed internet that can transmit large amounts of data quickly and efficiently. The entry of Starlink into Indonesia has introduced new dynamics in the country’s telecommunications sector. The government’s regulatory response, in the form of licensing restrictions on the sale of devices and the use of services, aims to maintain legal certainty, protect digital sovereignty, and safeguard local internet providers. This study aims to analyze the implications of licensing regulations on the restriction of Starlink and its impact on business competition. The research applies a normative juridical method through legislative, conceptual, and comparative approaches. The results show that the restrictions are based on the need to preserve legal certainty, digital sovereignty, and the protection of local internet services. However, such policies may competition dynamics. Overprotective regulation may slow technological progress, while overly open regulations could threaten local industries. Therefore, proportional and adaptive policies are required to balance domestic market protection, consumer interests and access to global innovation.